2015
DOI: 10.2174/1566524015666151026095730
|View full text |Cite
|
Sign up to set email alerts
|

Cell-in-cell phenomenon: A New Paradigm in Life Sciences.

Abstract: Cell-in-cell, a phenomenon characterized by one or more viable cells entering actively into another cell, was observed more than a century and has only attracted more attention in recent years and is becoming a new hot topic in the biological field, owing its biological significance in evolutionary as well as physiological and pathological relevance in development, homeostasis and diseases. In this paper we focus on the diversity, evolutionary conservatism and clinical implication of cell-in-cell as well as la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Invasion giving rise to the cell-in-cell phenomenon has been reported in a number of tissues, including epithelia 30,31 . Invasion is an active process and contrasts with phagocytosis, which involves uptake of an apoptotic cell.…”
Section: Resultsmentioning
confidence: 99%
“…Invasion giving rise to the cell-in-cell phenomenon has been reported in a number of tissues, including epithelia 30,31 . Invasion is an active process and contrasts with phagocytosis, which involves uptake of an apoptotic cell.…”
Section: Resultsmentioning
confidence: 99%
“…Some involve phagocytosis (see (Brown et al 2015)), while others involve non-phagocytic mechanisms, such as suicidal emperipolesis (Sierro et al 2015), entosis (Florey et al 2015), cell cannibalism (Lozupone and Fais 2015), and others (Wang 2015). These mechanisms can be broadly characterized as heterotypic (occurring between different cell types) or homotypic (occurring between the same cell type), and lead to the formation of cell-in-cell structures (Overholtzer and Brugge 2008; Wang 2015). In this review we discuss the detailed molecular mechanism of one of these cell-in-cell processes, entosis, as well as the consequences of entosis on cell populations, and evidence that entosis occurs in vivo in normal and diseased contexts.…”
Section: Cannibalistic Cell Deathmentioning
confidence: 99%
“…Among these, multiple mechanisms have been found where viable cells can become engulfed or cannibalized and then killed (Overholtzer and Brugge 2008; Overholtzer and Wang 2015; Wang 2015; Wang and Wang 2015). These programs, termed entosis (Florey et al 2015; Overholtzer et al 2007), phagoptosis (Brown et al 2015), suicidal emperipolesis (Sierro et al 2015), homotypic cell cannibalism (Cano et al 2012), emperitosis (Wang et al 2013), and cannibalism (Lugini et al 2006), appear to differ fundamentally from most classic forms of cell suicide, due to the requirement of engulfing cells for cell death execution.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, pathologists have seen a type of special structures, characterized by morphologically normal cells enclosed by other cells, in a variety of human tumor samples. Some terms, such as “cell cannibalism” and “cytophagocytosis” and the like, were used to describe these unique structures, which were recently given a unified name “cell-in-cell” structures (CICs) 1 2 . Based on the cells involving in structure formation, CICs could roughly be classified into two categories: 1) homotypic CICs, in which structures are formed between cells of same type like epithelial cells; 2) heterotypic CICs, where cells of different types such as epithelia and lymphocytes participate in structure formation 2 .…”
mentioning
confidence: 99%
“…Therefore, one process responsible for homotypic CICs formation, entosis, was recommended as a death mechanism by the Nomenclature Committee on Cell Death 9 . Recent progresses have shown that CICs formation played important roles in immune homeostasis 5 and tumorigenesis 10 11 12 , and is likely an evolutionarily conserved phenomenon 2 . Mechanistically, CICs formation may reflect the competitive nature of confronted cells 12 , representing a novel mechanism of cell competition 13 .…”
mentioning
confidence: 99%